2012
DOI: 10.3748/wjg.v18.i46.6856
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of TLR4 and TLR2 polymorphisms in inflammatory bowel disease in a Guangxi Zhuang population

Abstract: The TLR4 gene Asp299Gly, Thr399Ile and TLR2 gene Arg753Gln, Arg677Trp polymorphisms may not be associated with IBD in the Zhuang population from the Guangxi Zhuang Autonomous Region of China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Our results confirmed that the two polymorphisms of TLR2 did not exist in subjects who exhibited the wild-type allele for Arg753Gln and Arg677Trp. These results are consistent with previous studies in India (19,20) and China (21,22).…”
Section: Discussionsupporting
confidence: 83%
“…Our results confirmed that the two polymorphisms of TLR2 did not exist in subjects who exhibited the wild-type allele for Arg753Gln and Arg677Trp. These results are consistent with previous studies in India (19,20) and China (21,22).…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, the expression of TLR4, p-p65, and p-IκB was higher in the DSS group than that in the control group, but this trend was reversed by high dose of L. plantarum L15 administration. In addition, TLR4 up-regulation has been detected during intestinal examination of IBD patients, its activation by DSS administration has been reported ( 71 , 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…TLR2 receptors are elevated and associated with increasing BMI values in obese children . Arg753Gln polymorphisms may not be associated with IBD in the Guangxi Zhuang population of China . Studies in Turkish children indicate that the Arg753Gln TLR2 polymorphism influences the speed of progression from infection to tuberculosis .…”
Section: Discussionmentioning
confidence: 93%
“…TLR2 is one of the most important innate immune receptors that play important roles in recognizing the pathogens and producing inflammatory cytokines . Recently, the role of TLR2 gene polymorphisms has been evaluated in systemic inflammatory diseases such as coronary artery disease , children obesity and inflammatory bowel disease (IBD) . TLR2 receptors are elevated and associated with increasing BMI values in obese children .…”
Section: Discussionmentioning
confidence: 99%